Opening for Business : Myanmar Diagnostic Trade Integration Study - World Bank Group (World Bank, Washington, DC, 2016)
As part of the Enhanced Integrated Framework (EIF) program for Trade-Related Assistance to Least Developed Countries (LCDs), which Myanmar joined in April 2013, the Government of Myanmar has asked the World Bank Group (WBG) to be the implementing agency for a Diagnostic Trade Integration Study (DTIS). The general objectives of a DTIS are: (i) to assist the government in mainstreaming trade and competitiveness in the country’s overall development strategy; (ii) to provide a diagnostic and analytical tool to prioritize and sequence key reforms in the area of trade and competitiveness; and (iii) to provide a platform for development partners to coordinate action and align trade related assistance with government priorities. This DTIS has identified a number of domestic and external constraints facing Myanmar as it strives to leverage regional and global integration for inclusive, export-led growth. Based on this, the current report provides analytical input on the linkages between trade and poverty, and highlights key steps to remove bottlenecks in terms of trade policy and trade facilitation.